One-pot synthesis of sub-10 nm LiNbO3 nanocrystals exhibiting a tunable optical second harmonic response. Issue 6 (29th April 2019) - Ali, Rana Faryad; Bilton, Matthew; Gates, Byron D.
Abstract : Sub-10 nm single-crystalline LiNbO3, nanocrystals that exhibit a tunable non-linear optical response were prepared by a one-pot solution-phase synthesis. Abstract : Nanophotonics, dealing with the properties of light interacting with nanometer scale materials and structures, has emerged as a sought after platform for sensing and imaging applications, and is impacting fields that include advanced information technology, signal processing circuits, and cryptography. Lithium niobate (LiNbO3 ) is a unique photonic material, often referred to as the "silicon of photonics" due to its excellent optical properties. In this article, we introduce a solution-phase method to prepare single-crystalline LiNbO3 nanoparticles with average diameters of 7 nm. This one-pot approach forms well-dispersed LiNbO3 nanocrystals without additional organic additives ( e.g., surfactants) to control growth and aggregation of the nanoparticles. Formation of these LiNbO3 nanocrystals proceeds through a non-aqueous sol–gel reaction, in which lithium hydroxide and niobium hydroxide species were generated in situ . The reaction proceeded through both a condensation and crystallization of these reactants to form the solid nanoparticles. These nanocrystals of LiNbO3 were active for optical second harmonic generation (SHG) with a tunable response from 400 to 500 nm. These nanoparticles could enable further development of non-linear optical techniques such as SHG microscopy for bioimaging, which requires the dimensions of nanoparticles to be well below 100 nm.